Lithium metal battery, manufacturing method thereof, energy storage system and electric equipment

By forming a dense double-layer SEI film in lithium metal batteries through a multi-stage liquid injection process, the problems of interface stability and dendrite suppression of lithium metal anodes are solved, and performance is improved under high voltage conditions, making it suitable for long-term energy storage systems.

CN120978226AActive Publication Date: 2025-11-18ZHEJIANG JINKO ENERGY STORAGE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511503737.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2025-11-18
Estimated Expiration
2045-10-20

AI Technical Summary

Technical Problem

During charging and discharging, lithium metal anodes are prone to side reactions with electrolytes, forming an unstable SEI film. This leads to low coulombic efficiency, reduced cycle life, and safety hazards. In particular, interface stability and dendrite suppression are difficult to effectively address under high voltage conditions.

Method used

A multi-stage electrolyte injection process is adopted. First, a first electrolyte, mainly composed of low-viscosity ether solvent, is injected to form the inner SEI base. Then, a high-concentration electrolyte, containing lithium salt and TTFEB components, is injected in a pulse manner to finely control the interfacial decomposition rate and product deposition, forming a dense double-layer SEI film.

Benefits of technology

It significantly improves the interface stability, ion/electron transport selectivity, and lithium dendrite suppression capability of lithium metal batteries, thereby enhancing the cycle life, coulombic efficiency, and safety performance of the batteries, making them suitable for long-term energy storage systems under high-voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120978226A_ABST
    Figure CN120978226A_ABST
Patent Text Reader

Abstract

The invention provides a lithium metal battery and a manufacturing method thereof, an energy storage system and electric equipment, which are beneficial to improving the performance of the lithium metal battery. The method comprises the following steps: providing a positive plate, a negative current collector and a diaphragm; winding or laminating the positive plate, the negative current collector and the diaphragm, and putting into a shell to form an initial battery cell; a first electrolyte is injected into the initial battery cell, the first electrolyte comprises a lithium salt, lithium nitrate and a solvent, the solvent at least contains 70 wt% or above of a short-chain ether solvent, and the number of carbon atoms of the short-chain ether solvent is smaller than or equal to 6; performing a first formation process on the initial battery cell; a second electrolyte is injected into the initial battery cell in a pulse type liquid injection mode, the second electrolyte comprises a lithium salt, 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether and a solvent, and the molar concentration of the lithium salt in the second electrolyte is larger than that of the lithium salt in the first electrolyte; and performing a second formation process on the initial battery cell to form the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium metal batteries, and in particular to a lithium metal battery and its manufacturing method, energy storage system and electrical equipment. Background Technology

[0002] With the continued growth in global demand for clean energy and efficient energy storage technologies, the development of next-generation rechargeable batteries with higher energy density has become a research hotspot and an industry frontier. Lithium metal anodes are considered one of the most promising anode materials due to their extremely high theoretical specific capacity (3860 mAh / g) and extremely low electrochemical potential (-3.04 V vs. standard hydrogen electrode). When matched with high-voltage cathode materials, they are expected to achieve a significant breakthrough in battery energy density (e.g., exceeding 500 Wh / kg).

[0003] However, the commercial application of lithium metal anodes still faces significant challenges. Lithium metal itself is chemically highly reactive and readily undergoes side reactions with the electrolyte during charging and discharging, forming an unstable and continuously growing solid electrolyte interphase (SEI) film. This unstable SEI film not only consumes active lithium and electrolyte, leading to low coulombic efficiency and reduced cycle life, but more seriously, it is difficult to effectively suppress the formation and penetration of lithium dendrites, thereby causing serious safety problems such as internal short circuits and even thermal runaway. Summary of the Invention

[0004] This application provides a lithium metal battery, its manufacturing method, energy storage system, and electrical equipment, which at least helps to improve the performance of lithium metal batteries.

[0005] According to some embodiments of this application, one aspect of this application provides a method for manufacturing a lithium metal battery, comprising: providing a positive electrode sheet, a negative electrode current collector, and a separator; winding or stacking the positive electrode sheet, negative electrode current collector, and separator and placing them into a casing to form an initial battery cell, wherein the separator is located between the positive electrode sheet and the negative electrode current collector; injecting a first electrolyte into the initial battery cell, the first electrolyte comprising a lithium salt, lithium nitrate, and a solvent, wherein the solvent contains at least 70 wt% of a short-chain ether solvent, and the short-chain ether solvent has 6 or fewer carbon atoms; performing a first formation process on the initial battery cell; injecting a second electrolyte into the initial battery cell using pulse injection, the second electrolyte comprising a lithium salt, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and a solvent, wherein the molar concentration of the lithium salt in the second electrolyte is greater than the molar concentration of the lithium salt in the first electrolyte; and performing a second formation process on the initial battery cell to form a lithium metal battery.

[0006] In some embodiments, the concentration of lithium salt in the first electrolyte is 0.3 mol / L to 2.5 mol / L; and the concentration of lithium salt in the second electrolyte is greater than 2.5 mol / L and less than or equal to 6.0 mol / L.

[0007] In some embodiments, the mass percentage of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether in the second electrolyte is 35wt% to 70wt%.

[0008] In some embodiments, the second formation process includes: performing a first charge-discharge cycle on the initial cell at a first rate, with the voltage range being a first voltage range; performing a second charge-discharge cycle on the initial cell at a second rate, with the voltage range being a second voltage range; and performing a third charge-discharge cycle on the initial cell at a third rate, with the voltage range being a third voltage range; wherein the third rate > the second rate > the first rate; the first voltage range is within the second voltage range, and the second voltage range is within the third voltage range.

[0009] In some embodiments, the first multiplier is 0.01C~0.15C, the second multiplier is 0.1C~0.5C, and the third multiplier is 0.2C~1.0C; the first voltage range is 2.0V~4.5V, the second voltage range is 1.5V~4.6V, and the third voltage range is 1.0V~4.8V.

[0010] In some embodiments, after performing a first formation process on the initial battery cell and before injecting a second electrolyte into the initial battery cell, the process further includes: a static aging process, which includes at least one aging cycle in which the initial battery cell is heated from a first temperature to a second temperature and then cooled back to the first temperature within a preset time.

[0011] In some embodiments, the preset time is 0.5h to 48h, the first temperature is 25℃ to 30℃, and the second temperature is 45℃ to 50℃.

[0012] In some embodiments, after the static aging process and before injecting the second electrolyte into the initial cell, the process includes: testing the interface impedance of the initial cell; if the interface impedance of the initial cell is in the range of 20Ω to 100Ω, then injecting the second electrolyte into the initial cell; if the interface impedance of the initial cell is greater than 100Ω, then performing the static aging process again; if the interface impedance of the initial cell is less than 20Ω, then performing a charge-discharge cycle of 0.02C once to twice.

[0013] In some embodiments, during the process of injecting the second electrolyte into the initial cell, the mass of electrolyte injected in each pulse is 5% to 50% of the mass of the second electrolyte, the pulse interval is 2 min to 60 min, and the number of pulses is 2 to 20.

[0014] In some embodiments, before injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is raised to a first preset temperature; during the process of injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is lowered from the first preset temperature to the second preset temperature.

[0015] In some embodiments, the solvent in the second electrolyte includes ether solvents and sulfone solvents, wherein the mass ratio of sulfone solvent to ether solvent is 20:80 to 80:20.

[0016] In some embodiments, the solvent in the first electrolyte further includes sulfone solvents; in the mixed system of the first electrolyte and the second electrolyte, the mass ratio of sulfone solvent to ether solvent is 20:80 to 50:50.

[0017] According to some embodiments of this application, another aspect of this application provides a lithium metal battery, which is prepared using the manufacturing method of the lithium metal battery in the above embodiments.

[0018] According to some embodiments of this application, another aspect of this application also provides an energy storage system, including a lithium metal battery as described in the above embodiments.

[0019] According to some embodiments of this application, in another aspect of this application, an electrical device is provided, the electrical device including a load and the lithium metal battery in the above embodiments; or, the electrical device including a load and the energy storage system in the above embodiments.

[0020] The technical solution provided in this application has at least the following advantages: In the lithium metal battery manufacturing method provided in this application embodiment, firstly, the basic construction of the negative electrode interface and the initial full wetting of the battery cell are carried out in the first stage, that is, the first electrolyte, which is mainly composed of low-viscosity ether solvent and rich in LiNO3, is injected and a first formation process is performed. The first stage is to utilize the excellent wettability of ether solvent on the negative electrode current collector, so that LiNO3 can preferentially and fully undergo a reduction reaction on the surface of the negative electrode current collector in a "dedicated" chemical environment with almost no competition from other film-forming additives (such as TTFEB). The purpose is to pre-construct a layer of Li3N / Li x NO yThe inner SEI layer, composed mainly of lithium-ion salts and TTFEB, possesses good mechanical flexibility and preliminary lithium-ion conductivity. Compared to the uneven and easily interfered LiNO3 film formation in traditional mixed electrolytes, this stage offers the advantage of providing a more stable and uniform ideal foundation for subsequent SEI growth. Secondly, after completing the initial electrochemical activation and stabilization of the LiNO3-derived layer, the second stage introduces a locally high-concentration electrolyte (LHCE) containing high-concentration lithium salts and TTFEB components. Pulsed injection, rather than a single rapid injection, is employed to precisely control the decomposition rate and product deposition process of TTFEB at the pre-treated negative electrode current collector interface. Through multiple "thin-layer growths" and intermediate "relaxation times," a more uniform, dense, and less defect-laden LiF-rich outer SEI film is formed. This differs from conventional injection methods where TTFEB may react too quickly or have uneven concentrations, resulting in a loose or incomplete LiF layer, thus allowing for more effective utilization of the electronic insulation and chemical stability properties of the LiF layer. This precisely engineered interface structure exhibits significant advantages over SEI films formed using traditional single-mixing processes, particularly in terms of interface stability, ion / electron transport selectivity, lithium dendrite suppression, and electrolyte decomposition barrier effects. This provides a comprehensive and significant improvement in cycle life, coulombic efficiency, and safety performance for high-voltage lithium metal batteries. Lithium metal batteries are expected to overcome existing bottlenecks, achieving a comprehensive improvement in energy density, cycle life, and safety performance, enabling high-capacity lithium metal batteries suitable for long-term energy storage applications, such as energy storage systems that can operate continuously for 4 to 8 hours at rated power. This will provide key technological support for the development of next-generation high-performance electrochemical energy storage systems. Attached Figure Description

[0021] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 A flowchart corresponding to the manufacturing method of the lithium metal battery provided in the embodiments of this application. Detailed Implementation

[0023] As can be seen from the background technology, the commercial application of lithium metal anodes still faces huge challenges.

[0024] To address these challenges, researchers have made significant efforts in electrolyte engineering, among which the Localized High Concentration Electrolyte (LHCE) strategy has shown considerable potential. LHCE aims to maintain a unique solvation structure around lithium ions by introducing inert or low-polarity diluents into high-concentration lithium salt-solvent complexes, thereby broadening the electrochemical window, improving compatibility with lithium metal, and simultaneously reducing overall viscosity and increasing ionic conductivity.

[0025] Nevertheless, even with LHCE, the stability of electrolyte components (including solvents, lithium salts, and diluents) at the positive and negative electrode interfaces under high voltage conditions (e.g., 4.5V and above) still faces severe challenges. Furthermore, how to effectively construct an ideal SEI film on the lithium metal surface in situ that can adapt to long-term cycling, suppress dendrite growth, and maintain high ionic conductivity remains a key technical bottleneck that urgently needs to be solved in this field.

[0026] Therefore, developing innovative interface control strategies, especially optimizing the SEI formation process from the perspective of battery manufacturing technology, is of great significance for promoting the practical application of high-voltage lithium metal batteries.

[0027] To address the interfacial stability issue of lithium metal anodes, related technologies mainly focus on optimizing electrolyte components (such as developing novel lithium salts, solvents, or additives), constructing artificial SEI films, and designing electrode structures.

[0028] In electrolyte composition optimization engineering, utilizing specific additives to form an in-situ SEI film during the first charge-discharge cycle is a common and economical strategy. For example, lithium nitrate (LiNO3) has been widely studied as an effective SEI film-forming additive for lithium metal anodes. It can be reduced on the lithium surface to form a film containing Li3N and Li... x NO y A protective layer of equal components is used, which are believed to help passivate the lithium metal surface and improve lithium deposition behavior to some extent. In addition, fluorinated compounds, such as fluoroethylene carbonate (FEC) or certain hydrofluoroethers, are also used as additives or diluents, designed to introduce highly stable inorganic fluorides into the SEI through their decomposition products (such as LiF). LiF is considered to have good electronic insulation and certain Li... + Conductivity helps to build a more stable SEI.

[0029] In locally high-concentration electrolytes (LHCE), the basic principle is to increase the coordination number of lithium salts with specific solvent molecules, thereby reducing the number of free solvent molecules, which alters the solvation structure of lithium ions, improves the reduction stability of the solvent, and may promote more uniform lithium deposition. To address the high viscosity and low conductivity issues of LHCE, low-viscosity, low-polarity diluents, such as hydrofluoroethers (HFE), are typically introduced. By mixing all components at once and injecting them into the lithium metal battery, the SEI film is formed through spontaneous or competitive reactions of the components on the electrode surface during subsequent electroforming.

[0030] Despite some progress in improving the interface of lithium metal batteries, existing technologies still have many problems and limitations.

[0031] First, for electrolyte systems containing multiple functional additives, such as LiNO3 and fluorinated compounds (e.g., 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, TTFEB), the traditional one-step mixing and injection process and conventional formation techniques often result in these additives playing a simultaneous and competitive role in SEI formation. This disordered and competitive film-forming process makes it difficult to ensure that each component can exert its maximum effectiveness under optimal conditions, leading to SEI films that fail to achieve ideal chemical composition, microstructure, thickness uniformity, and functional gradient distribution. For example, the decomposition products of LiNO3 and TTFEB may mix disorderly, failing to form an optimized structure with specific functional stratification (e.g., an inner layer of mechanical stability and an outer layer of dense insulation), thus limiting the full realization of their synergistic protective effect.

[0032] Secondly, while locally high-concentration electrolytes (LHCE) theoretically offer advantages, their high salt concentration and unique solvation structure can lead to persistently high viscosity and poor wettability, especially in complex real-world electrode pore structures. This not only affects ion transport rates but can also cause uneven SEI formation in different regions, creating potential hazards for lithium dendrite initiation and growth. Currently, there is insufficient focus on the precise control of LHCE injection processes and interface formation.

[0033] In addition, although some diluents, such as TTFEB, are expected to participate in SEI construction (e.g., forming LiF) in addition to being physical diluents, the kinetics, product morphology and distribution of their decomposition reaction are difficult to control precisely in conventional one-step mixing and formation processes. This may result in the LiF layer being non-dense or unevenly distributed, thus affecting its protective effect.

[0034] In summary, existing technologies primarily focus on the static component design of the electrolyte, lacking technological means for dynamic and orderly control of the multi-component synergistic film formation process. This makes it difficult to optimize the structure and performance of the SEI film, thus limiting further improvements in the overall performance of high-voltage lithium metal batteries. Therefore, there is an urgent need to develop an innovative process capable of precisely controlling the interface formation process to fully leverage the synergistic advantages of various functional components in a specific electrolyte system.

[0035] This application provides a lithium metal battery, its manufacturing method, energy storage system, and electrical equipment, which at least helps to improve the performance of lithium metal batteries.

[0036] In the description of the embodiments of this application, the technical terms "first", "second", etc. are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0037] In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0038] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0039] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.

[0040] Figure 1 A flowchart corresponding to the manufacturing method of the lithium metal battery provided in the embodiments of this application.

[0041] refer to Figure 1 According to some embodiments of this application, one aspect of this application provides a method for manufacturing a lithium metal battery, including: S101 provides positive electrode plates, negative electrode current collectors, and separators; S102. After the positive electrode sheet, negative electrode current collector and separator are wound or stacked, they are placed into the housing to form the initial cell. The separator is located between the positive electrode sheet and the negative electrode current collector. S103. Inject a first electrolyte into the initial cell. The first electrolyte includes lithium salt, lithium nitrate and solvent, and the solvent contains at least 70 wt% of short-chain ether solvent, and the number of carbon atoms in the short-chain ether solvent is less than or equal to 6. S104. Perform the first formation process on the initial battery cell; S105. A second electrolyte is injected into the initial cell using a pulse injection method. The second electrolyte includes lithium salt, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and a solvent. The molar concentration of lithium salt in the second electrolyte is greater than the molar concentration of lithium salt in the first electrolyte. S106. Perform a second formation process on the initial cell to form a lithium metal battery.

[0042] In the lithium metal battery manufacturing method provided in this application embodiment, firstly, the basic construction of the negative electrode interface and the initial full wetting of the battery cell are carried out in the first stage, that is, the first electrolyte, which is mainly composed of low-viscosity ether solvent and rich in LiNO3, is injected and a first formation process is performed. The first stage is to utilize the excellent wettability of ether solvent on the negative electrode current collector, so that LiNO3 can preferentially and fully undergo a reduction reaction on the surface of the negative electrode current collector in a "dedicated" chemical environment with almost no competition from other film-forming additives (such as TTFEB). The purpose is to pre-construct a layer of Li3N / Li x NO y The inner SEI layer, composed mainly of lithium-ion salts and TTFEB, possesses good mechanical flexibility and preliminary lithium-ion conductivity. Compared to the uneven and easily interfered LiNO3 film formation in traditional mixed electrolytes, this stage offers the advantage of providing a more stable and uniform ideal foundation for subsequent SEI growth. Secondly, after completing the initial electrochemical activation and stabilization of the LiNO3-derived layer, the second stage introduces a locally high-concentration electrolyte (LHCE) containing high-concentration lithium salts and TTFEB components. Pulsed injection, rather than a single rapid injection, is employed to precisely control the decomposition rate and product deposition process of TTFEB at the pre-treated negative electrode current collector interface. Through multiple "thin-layer growths" and intermediate "relaxation times," a more uniform, dense, and less defect-laden LiF-rich outer SEI film is formed. This differs from conventional injection methods where TTFEB may react too quickly or have uneven concentrations, resulting in a loose or incomplete LiF layer, thus allowing for more effective utilization of the electronic insulation and chemical stability properties of the LiF layer.

[0043] For high voltage (operating voltage not less than 4.5V vs Li / Li) +This multi-stage synergistic electrolyte injection and interface control process for lithium metal batteries aims to fully leverage the potential of locally high-concentration electrolyte (LHCE) and overcome the problems of disordered SEI film formation, difficulty in maximizing component functions, and uneven interface structure and performance caused by traditional one-step mixing and injection processes. Through the aforementioned multi-stage, multi-dimensional synergistic process design, a functionally graded SEI structure was controllably constructed on the surface of the negative electrode current collector. This SEI exhibits a distinct bilayer structure: the inner layer consists of LiNO3 reduction products (mainly including Li3N and Li...). x NO y The SEI film, composed of Li₂O and other components, exhibits excellent mechanical compliance and ion transport properties. The outer layer is rich in LiF microcrystalline networks formed by the electrochemical decomposition of TTFEB, providing a highly dense electron barrier. This precisely engineered interface structure demonstrates significant advantages over traditional single-mixing processes, particularly in interface stability, ion / electron transport selectivity, lithium dendrite suppression, and electrolyte decomposition barrier effects. This provides a comprehensive and significant improvement in cycle life, coulombic efficiency, and safety performance for high-voltage lithium metal batteries.

[0044] In S101, the positive electrode sheet may include a positive current collector and a positive electrode material layer covering the surface of the positive current collector. The positive electrode material layer includes a positive electrode active material, a binder, and a conductive agent.

[0045] The positive current collector can be selected from conductive substrates suitable for high-voltage systems, such as aluminum foil or carbon-coated aluminum foil.

[0046] The formulation of the positive electrode material layer may include 85wt% to 98wt% of positive electrode active material, 2wt% to 10wt% of binder and 2wt% to 8wt% of conductive agent.

[0047] Positive electrode active materials can be composed of a variety of materials, including layered oxide positive electrode materials, spinel structure positive electrode materials, polyanion positive electrode materials, lithium-rich manganese-based positive electrode materials, transition metal fluoride positive electrode materials, and organic positive electrode materials.

[0048] Among them, the chemical formula of the layered oxide cathode material can be Li x MO2, where M is a combination of transition metal elements such as Ni, Co, Mn, and Al, such as LiNi. 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.15 Al 0.05High-nickel materials such as O2 (NCA). Typical examples of spinel structure cathode materials are LiMn2O4 and high-voltage spinel LiNi. 0.5 Mn 1.5 O4 exhibits high safety and good rate performance. The general formula for polyanion cathode materials is Li. x MPO4 (where M represents Fe, Mn, Co, V, etc.), with LiFePO4 being widely used due to its excellent cycle stability and safety. Lithium-rich manganese-based cathode materials (xLi2MnO3·(1-x)LiMO2, where M represents Ni, Co, etc.) have attracted attention due to their high specific capacity (>250 mAh / g). Transition metal fluoride cathode materials (such as FeF3 and CoF3) exhibit high voltage plateaus and high energy densities. Organic cathode materials (such as polymers containing carbonyl or quinone groups) are potential candidates due to their environmental friendliness and structural designability.

[0049] The adhesive may be selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), or polyacrylic acid (PAA). The conductive agent may be selected from one or more of conductive carbon black, graphene, carbon nanotubes, or graphite.

[0050] The conductive agent can be selected from one or more of conductive carbon black, graphene, carbon nanotubes or graphite.

[0051] Lithium metal-based materials can be used as negative electrode current collectors, encompassing various forms and modification strategies. As a basic form, pure lithium metal negative electrodes typically exist as lithium foil or lithium layers, with thicknesses ranging from the traditional 50-500 micrometers to ultrathin 5-50 micrometers. Ultrathin lithium foil designs help improve battery energy density and reduce dead lithium formation. In terms of morphology optimization, surface-structured lithium metals (such as lithium foils with specific micro / nano structures) and three-dimensional lithium metals (such as porous lithium or lithium filled in a conductive framework) can effectively reduce local current density and promote uniform deposition. Lithium alloy negative electrodes include lithium-main group metal alloys (Li-Al, Li-Si, Li-Sn, Li-Ge, etc.) and lithium-transition metal alloys, which mitigate dendrite growth by forming a stable phase. Lithium-based composite negative electrodes, such as lithium-carbon composites, utilize the conductivity and structural stability of carbon materials to enhance negative electrode performance. Artificial SEI film technology significantly improves interfacial stability by pre-constructing organic (e.g., conductive polymers), inorganic (e.g., LiF, Li3N, Al2O3, etc.), or organic / inorganic composite protective layers on the lithium surface. Anode-free technology uses specially treated copper foil current collectors as lithium deposition substrates, and can also use surface-modified copper foil (e.g., carbon-coated copper foil, lithiophilic coated copper foil), or other special materials.

[0052] Membranes can be made from a variety of materials, including polypropylene (PP), polyethylene (PE), PP / PE / PP three-layer composite membranes, ceramic-coated membranes, high-strength polymer membranes, and functionalized composite membranes. PP and PE porous membranes typically have a thickness of 12-25 micrometers and a porosity of 30%-50%, exhibiting good mechanical strength and chemical stability. Ceramic-coated membranes, with a coating of ceramic materials such as Al2O3, SiO2, and TiO2 (coating thickness 2-5 micrometers) onto a polyolefin-based membrane, improve high-temperature resistance (thermal shut-off temperature >160℃) and puncture resistance. High-strength polymer membranes (such as polyimide (PI), polyethylene terephthalate (PET), and aramid nanofiber membranes) possess excellent mechanical properties and high-temperature resistance. Functionalized composite membranes (such as membranes with solid electrolyte coatings or lithiophilic coatings) can further enhance lithium deposition stability.

[0053] In step S102, after the initial cell assembly is completed, drying and helium insulation testing may be included. Drying involves vacuum baking the initial cells at 80°C to 120°C for 12 to 24 hours to remove residual moisture, ensuring the internal moisture content of the initial cells is below 20 ppm. Helium insulation testing is then performed to confirm that the initial cells are well-sealed and have no leakage risk. The weight of the initial cells before electrolyte injection is recorded as a baseline for subsequent electrolyte injection volume control.

[0054] In S103, the first electrolyte is injected into a glove box under an inert gas atmosphere with O2 content less than 1 ppm, H2O content less than 1 ppm, dew point below -45℃, and temperature between 10℃ and 40℃. The injection equipment uses a precision metering pump with an injection rate of 0.1 mL / min to 10 mL / min and an injection accuracy of ±0.05 mL. The first electrolyte injection volume is calculated based on the battery capacity; a typical 18650 battery (3 Ah) requires 1.0 mL to 2.0 mL, while pouch batteries are calculated at 0.8 mL / Ah to 1.2 mL / Ah. The electrolyte is weighed immediately after injection to confirm the actual volume.

[0055] In the first electrolyte, the concentration of lithium salt is 0.3 mol / L to 2.5 mol / L, specifically 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.3 mol / L, or 2.5 mol / L.

[0056] In the first electrolyte, the lithium salt can be selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(pentafluoroethylsulfonyl)imide (LiBETI). These fluorinated imide salts exhibit excellent thermal and electrochemical stability. Auxiliary lithium salts such as lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium tetrafluoro(oxalate)phosphate (LiTFOP), and lithium difluorobis(oxalate)phosphate (LiDFBOP) can be selectively added to optimize the overall performance of the electrolyte.

[0057] The lithium salt in the first electrolyte can be selected from at least one of LiFSI, LiTFSI or LiPF6, which provides the necessary ionic conductivity without excessively interfering with the film formation process of LiNO3.

[0058] Lithium nitrate (LiNO3), as a key inner SEI film-forming additive in the first electrolyte, can preferentially reduce and form a film rich in Li3N and Li on the surface of the negative electrode current collector. x NO y A protective layer of equal components.

[0059] The content of LiNO3 in the first electrolyte is 2wt%~20wt%, for example 2wt%~4wt%, 4wt%~6wt%, 6wt%~12wt%, 12wt%~15wt%, specifically 2wt%, 2.5wt%, 4wt%, 5.5wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, or 15wt%.

[0060] The first electrolyte is mainly composed of ether solvents, with low-viscosity short-chain ether solvents as the main components. The short-chain ether solvents include one or more of the following: 1,2-dimethoxyethane (DME), 1,3-dioxolane (DOL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,4-dioxane, methyl tert-butyl ether (MTBE), diethyl ether, dipropyl ether, diisopropyl ether, ethylpropyl ether, cyclopentyl methyl ether, and diethylene glycol dimethyl ether (DEGDME or G2).

[0061] In some embodiments, the solvent may further include medium- to long-chain ether solvents having a carbon number greater than 6 and less than or equal to 10, wherein the mass ratio of short-chain ether solvent to medium- to long-chain ether solvent is 70:30 to 98:2, for example 70:30, 75:25, 80:20, 83:17, 86:14, 90:10, 95:5, or 98:2. This ratio ensures both good ionic conductivity and maintains an appropriate solvation structure.

[0062] Medium- and long-chain ethers may be selected from one or more of the following: triethylene glycol dimethyl ether (TEGDME or G3), tetraethylene glycol dimethyl ether (TETRAGLYME or G4), pentaethylene glycol dimethyl ether (G5), polyethylene glycol dimethyl ether (average molecular weight 200~2000), diethylene glycol diethyl ether, triethylene glycol diethyl ether, and crown ether compounds.

[0063] In the first electrolyte, the solvent may also include sulfone solvents. The introduction of sulfone solvents is intended to improve the oxidation stability of the electrolyte system, enabling it to operate stably under high voltage conditions.

[0064] Sulfonate solvents include cyclic sulfonate solvents, chain sulfonate solvents, and fluorinated sulfonate solvents. Cyclic sulfonates include sulfolane (SL), 3-methylsulfolane, 2,4-dimethylsulfolane, cyclopentyl sulfone, and cyclohexyl sulfone; chain sulfonates include dimethyl sulfone (DMS), methyl ethyl sulfone, ethyl methyl sulfone (EMS), diethyl sulfone, methyl propyl sulfone, methyl isopropyl sulfone, and ethyl propyl sulfone; fluorinated sulfonates include fluorosulfolane, trifluoromethyl methyl sulfone, and trifluoromethyl ethyl sulfone. Optionally, sulfolane is used as a sulfonate solvent.

[0065] The content of sulfone solvent in the first electrolyte shall not exceed 5 wt%, for example, it can be 0.1 wt%, 0.5 wt%, 1 wt%, 1.3 wt%, 1.8 wt%, 2 wt%, 2.2 wt%, 2.5 wt%, 2.8 wt%, 3 wt%, 3.3 wt%, 3.6 wt%, 3.9 wt%, 4 wt%, 4.4 wt%, or 5 wt%.

[0066] The first electrolyte may also contain 0wt% to 8wt% of auxiliary additives, such as lithium difluorophosphate (0.1wt% to 2wt%), tris(trimethylsilane) phosphite TMSP (0.1wt% to 1wt%), and trace amounts of FEC (not exceeding 2wt%), to fine-tune the performance of the initial SEI layer.

[0067] Auxiliary additives also include SEI modifiers such as fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfate (ES), propylene sulfate (PS), 1,3-propane sulpholactone, and 1,4-butane sulpholactone, which can improve the mechanical properties of SEI; and stabilizers such as tris(trimethylsilane) phosphate (TMSP), tris(trimethylsilane) phosphite (TMSPi), and tris(2,3-propane) phosphite. 2,2-Trifluoroethyl ester (TTFPi) and other similar agents can improve high-voltage stability; flame retardants such as trimethyl phosphate (TMP), triethyl phosphate (TEP), and triphenyl phosphate (TPP) can enhance safety; other hydrofluoroethers such as bis(2,2,2-trifluoroethyl) ether (BTFE), 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether (OPTFE), and 1,1,1,3,3,3-hexafluoroisopropyl methyl ether (HFPM) can be used as auxiliary diluents.

[0068] The first electrolyte accounts for 65wt% to 90wt% of the total injected electrolyte, for example, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, or 90wt%.

[0069] Total electrolyte volume refers to the total mass of electrolyte that needs to be injected into the initial battery cell.

[0070] After the first electrolyte is injected and before the first formation process, the initial cell with the injected electrolyte can be transferred to a constant temperature chamber and left to stand at 25℃~35℃ for 2h~4h for preliminary wetting. This mild condition is conducive to the selective reduction of LiNO3 on the lithium anode surface, forming a lithium anode rich in Li3N and Li. x NO y The inner SEI base layer is then subjected to vacuum-pressure cycling treatment: first, the vacuum is evacuated to -0.08MPa and held for 10 minutes, then nitrogen gas is introduced at 0.2MPa and held for 5 minutes, and the cycle is repeated 3 to 5 times to promote the full penetration of the first electrolyte into the electrode pores.

[0071] In S104, the first formation process is carried out in a constant temperature and humidity chamber, with the temperature controlled at 30℃±2℃ and the humidity controlled within the range of 30%RH~50%RH to ensure the appropriateness of the reaction kinetics.

[0072] The current range of the first formation process is 0.01C to 0.1C, optionally 0.02C to 0.05C. A lower current rate avoids an excessively fast reaction rate that could lead to a porous SEI structure. The voltage window of the first formation process ranges from open-circuit voltage to 4.5V, optionally 2.0V to 4.3V. The first formation process can include multiple charge-discharge cycles, ranging from 1 to 10 cycles, optionally 3 to 4 cycles. The charging rate and voltage range during different charge-discharge cycles can be the same or different.

[0073] The specific first formation process may include: (1) standing for 30 minutes to stabilize the voltage; (2) charging at a constant current of 0.02C to 3.0V to form an initial SEI film; (3) standing for 10 minutes to allow the voltage to relax; (4) charging at a constant current of 0.05C to 3.8V to continue growing the SEI film; (5) discharging at a constant current of 0.05C to 2.5V to stabilize the SEI film; (6) repeating steps (4) and (5) twice to optimize the SEI film.

[0074] In some embodiments, after the initial cell undergoes a first formation process and before injecting a second electrolyte into the initial cell, a static aging process is further included. This static aging process comprises at least one aging cycle, in which the initial cell is heated from a first temperature to a second temperature and then cooled back to the first temperature within a preset time. This process promotes the structural rearrangement and densification of the inner SEI layer formed in the first stage. During the aging process, the reduction products of LiNO3 undergo self-assembly optimization, forming a more stable and uniform protective layer, laying a good foundation for the interface strengthening in the second stage.

[0075] The first and second temperatures in different aging cycles can be the same or different.

[0076] The preset time is 0.5h~48h, the first temperature is 25℃~30℃, and the second temperature is 45℃~50℃.

[0077] For example, after the first formation process is completed, the initial cell is kept at 35°C for 4 hours, then the initial cell is heated to 45°C and kept at 45°C for 2 hours, and then the initial cell is cooled to 35°C. This is considered one aging cycle. In order to promote the structural rearrangement and densification of the inner SEI, multiple aging cycles can be selected.

[0078] After the static aging process, before injecting the second electrolyte into the initial cell, the process may further include: testing the interface impedance of the initial cell; if the interface impedance of the initial cell is in the range of 20Ω to 100Ω, then injecting the second electrolyte into the initial cell; if the interface impedance of the initial cell is greater than 100Ω, then performing the static aging process again; if the interface impedance of the initial cell is less than 20Ω, then performing a charge-discharge cycle of 0.02C once to twice.

[0079] For example, the quality of the SEI interface can be evaluated by electrochemical impedance spectroscopy (EIS) under the following test conditions: frequency of 100 kHz to 0.01 Hz, amplitude of 10 mV, temperature of 25 °C, and state of charge (SOC) of 50%.

[0080] In S105, an electrolyte containing high concentrations of lithium salt and TTFEB is introduced through a second electrolyte to complete the in-situ construction of a local high-concentration system, and a dense LiF-rich outer layer is formed on the basis of the pretreated inner SEI layer.

[0081] In the second electrolyte, the concentration of lithium salt is greater than 2.5 mol / L and less than or equal to 6.0 mol / L, for example, it can be 2.6 mol / L, 2.8 mol / L, 3 mol / L, 3.6 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L or 6 mol / L.

[0082] In the second electrolyte, the lithium salt can be selected from LiFSI and / or LiTFSI to facilitate the formation of a locally high-concentration electrolyte system.

[0083] In the mixed system of the first electrolyte and the second electrolyte, the total molar concentration of lithium salt ranges from 1.5 mol / L to 5.5 mol / L, for example, 1.5 mol / L to 2.0 mol / L, 2.0 mol / L to 3.5 mol / L, 3.5 mol / L to 4.5 mol / L, or 4.5 mol / L to 5.5 mol / L, to ensure that the electrolyte as a whole forms an effective local high-concentration solvation structure.

[0084] In the second electrolyte, the mass percentage of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTFEB) is 35wt% to 70wt%, for example, 35wt%, 38wt%, 40wt%, 43wt%, 46wt%, 48wt%, 50wt%, 51wt%, 54wt%, 58wt%, 60wt%, 62wt%, 65wt%, 68wt%, or 70wt%.

[0085] 1,1,2,2-Tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTFEB) serves a dual function: acting as a diluent to reduce system viscosity, and simultaneously as a key film-forming precursor for the outer SEI layer. Under electrochemical reduction conditions, TTFEB can generate a dense protective layer rich in LiF.

[0086] In the mixture of the first electrolyte and the second electrolyte, the content of TTFEB ranges from 5wt% to 50wt%, for example, 5wt% to 15wt%, 15wt% to 30wt%, 30wt% to 40wt%, or 40wt% to 50wt%.

[0087] In the second electrolyte, the solvents include ether solvents and sulfone solvents, wherein the mass ratio of sulfone solvent to ether solvent is 20:80 to 80:20, for example, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, or 80:20. The introduction of sulfone solvents enables the system to adapt to high voltage.

[0088] Sulfolane can be selected as a sulfone solvent in the second electrolyte.

[0089] In traditional LHCE designs, ether solvents and sulfone solvents are used in combination from the outset. However, there is an irreconcilable contradiction between the low oxidation potential (<4.0V) of ether solvents and the high viscosity of sulfone solvents. The first stage of this application uses a system primarily composed of ether solvents, with appropriate amounts of sulfone solvents mixed in to ensure sufficient wetting while creating favorable conditions for the preferential reaction of LiNO3. The second stage further enhances the oxidation stability and interfacial protection of the system by supplementing with a high concentration of TTFEB and additional sulfone solvents, enabling the final electrolyte to adapt to a high-voltage cathode.

[0090] This sequential introduction strategy does not simply avoid the shortcomings of each solvent, but rather fully leverages their respective advantages at specific stages. After ether solvents fulfill their role in constructing the negative electrode current collector interface, the introduction of sulfone solvents provides the necessary high voltage stability for the system. This design approach of "maximizing strengths and minimizing weaknesses, with complementary timing" represents the concept of electrolyte engineering moving from "static equilibrium" to "dynamic optimization."

[0091] Regardless of whether sulfone solvents are added to the first electrolyte, the mass ratio of sulfone solvents to ether solvents in the mixture of the first and second electrolytes is 20:80 to 50:50, for example, 20:80, 30:70, 40:60 or 50:50. This ratio design balances the requirements of oxidation stability and lithium metal compatibility.

[0092] The ether solvent in the second electrolyte can include short-chain ether solvents and medium- to long-chain ether solvents. In the mixed system of the first and second electrolytes, the mass ratio of short-chain ether solvents to medium- to long-chain ether solvents is 80:20 to 90:10, for example, 80:20, 82:18, 85:15, 88:12, or 90:10. This ratio ensures both good ionic conductivity and maintains an appropriate solvation structure.

[0093] In the mixed system of the first electrolyte and the second electrolyte, the content of LiNO3 ranges from 0.1wt% to 8wt%, for example, 0.5wt% to 1wt%, 1wt% to 3wt%, 3wt% to 5wt%, or 5wt% to 8wt%.

[0094] The second electrolyte may also contain 0wt% to 10wt% of auxiliary additives, such as FEC (1wt% to 5wt%), VC (0.5wt% to 3wt%), or other high voltage stabilizers.

[0095] In some embodiments, during the injection of the second electrolyte into the initial cell, the mass of electrolyte injected in each pulse is 5% to 50% of the mass of the second electrolyte, the pulse interval is 2 to 60 minutes, and the number of pulses is 2 to 20. The pulse injection of the second electrolyte can be performed using a programmable injection system to achieve precise timing and temperature control.

[0096] In some embodiments, before injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is raised to a first preset temperature; during the process of injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is lowered from the first preset temperature to the second preset temperature.

[0097] The first preset temperature is 40℃~50℃; the second preset temperature is 15℃~30℃.

[0098] The cooling rate of the initial cell temperature from the first preset temperature to the second preset temperature is 0.1℃ / min to 5℃ / min.

[0099] For example, the injection of the second electrolyte includes the following stages: (1) raising the temperature of the initial cell to 45°C; (2) injecting 20% ​​of the second electrolyte at 45°C at an injection rate of 2 mL / min, a pressure of 0.1 MPa, a time of 5 min, followed by a 15 min interval and then cooling down; (3) injecting 20% ​​of the second electrolyte at 42°C at an injection rate of 2 mL / min, a pressure of 0.15 MPa, a time of 5 min, followed by a 15 min interval and then cooling down; (4) injecting at 38°C (5) Inject 20% of the second electrolyte at 35°C at a rate of 1.5 mL / min, a pressure of 0.2 MPa, and a time of 8 min, followed by a 20 min interval and cooling down; (6) Inject 20% of the second electrolyte at 30°C at a rate of 1 mL / min, a pressure of 0.2 MPa, and a time of 8 min, followed by a 30 min interval and cooling down; (7) Inject 20% of the second electrolyte at 30°C at a rate of 1 mL / min, a pressure of 0.25 MPa, and a time of 10 min. During the interval after each pulse injection, the solution was kept at the corresponding temperature to allow TTFEB to slowly and uniformly decompose at the interface to form a LiF layer. The gradient temperature descent strategy ensured that the reaction kinetics gradually transitioned from rapid penetration to controlled decomposition.

[0100] Pulsed injection includes multiple pulse stages. As different pulse injection stages proceed, the injection rate gradually decreases, the interval time gradually increases, and the injection pressure gradually increases. This is designed to overcome the potentially high viscosity of LHCE (especially in the case of sulfone), and to ensure that the electrolyte can fully and uniformly penetrate into the microporous structure of the electrode during the multi-stage injection process, laying a physical basis for a uniform interfacial reaction.

[0101] After completing all electrolyte injection steps, the initial battery cell was left to stand in a constant temperature chamber for 12 hours to ensure uniform electrolyte distribution.

[0102] In S106, the second formation process includes: performing a first charge-discharge cycle on the initial cell using a first rate, with a voltage range of a first voltage range; performing a second charge-discharge cycle on the initial cell using a second rate, with a voltage range of a second voltage range; and performing a third charge-discharge cycle on the initial cell using a third rate, with a voltage range of a third voltage range; wherein the third rate > the second rate > the first rate; the first voltage range is within the second voltage range, and the second voltage range is within the third voltage range. This step-by-step formation aims to further stabilize and optimize the structure and performance of the entire SEI film after the initial formation of the multilayer SEI film structure through a mild and gradual electrochemical "curing" process, enabling it to better adapt to electrochemical and mechanical stresses during long-term cycling.

[0103] In some embodiments, the first multiplier is 0.01C~0.15C, the second multiplier is 0.1C~0.5C, and the third multiplier is 0.2C~1.0C; the first voltage range is 2.0V~4.5V, the second voltage range is 1.5V~4.6V, and the third voltage range is 1.0V~4.8V.

[0104] For example, the second formation process includes: (1) charging the initial cell from 0V to 4.2V at a charging rate of 0.05C, and then discharging the initial cell from 4.2V to 2.5V at a discharging rate of 0.05C, at a temperature of 25°C; (2) charging the initial cell from 2.5V to 4.3V and then discharging it to 2.5V at a charging and discharging rate of 0.08C for the first charge-discharge cycle, with 2 cycles, at a temperature of 28°C; (3) discharging the initial cell to 2.0V, and then charging the initial cell from 2.0V to 4.5V and then discharging it to 2.0V at a charging and discharging rate of 0.2C for the second charge-discharge cycle, with 2 cycles. (3) Charge the initial cell from 2.0V to 4.5V and then discharge it to 2.0V at a charge-discharge rate of 0.3C for the second charge-discharge cycle, with 2 cycles and a temperature of 32°C; (5) Discharge the initial cell to 1.5V, charge the initial cell from 1.5V to 4.6V and then discharge it to 1.5V at a charge-discharge rate of 0.5C for the third charge-discharge cycle, with 5 cycles and a temperature of 35°C; (6) Charge the initial cell from 1.5V to 4.7V and then discharge it to 1.5V at a charge-discharge rate of 1C for the third charge-discharge cycle, with 3 cycles and a temperature of 35°C.

[0105] The second formation process can be adjusted according to different battery systems and capacities. For high-nickel cathode systems, the upper limit of the formation voltage can be appropriately reduced (e.g., NCM811 should be controlled within 4.3V); for lithium iron phosphate systems, it can be simplified to a two-step formation process; for large-capacity batteries (>10Ah), the resting and aging time needs to be extended accordingly, and the electrolyte injection rate needs to be reduced. For anode-less systems, due to the extremely high requirements for SEI quality, the low-rate SOC of the first formation process should not be less than 60% to ensure the formation of a high-quality initial lithium layer on the current collector.

[0106] During the second formation process, the initial battery voltage, temperature, and internal resistance changes are continuously monitored. If any abnormality occurs (such as a sudden voltage drop or abnormal temperature rise), the process is immediately stopped and the cause is analyzed.

[0107] After the second formation process is completed, the battery cell is obtained. The battery cell undergoes comprehensive performance testing, such as capacity testing, rate testing, EIS testing, cycle testing, and safety testing.

[0108] The lithium metal battery manufacturing method provided in this application, through timing control, in the first stage, while meeting the basic wetting requirements of the initial cell, uses LiNO3 enrichment design to preferentially react and form flexible Li3N / Li during the first formation process. x NO yThe inner layer; in the second stage, LiF deposition is precisely controlled on the existing substrate by injecting a high-concentration TTFEB supplement solution. This time-sequential functional separation fundamentally solves the problem of SEI structural disorder caused by multi-component competitive reactions, and maximizes the performance of each functional component.

[0109] Compared to the traditional method of one-step mixing and single injection, where all components such as ether solvents, sulfone solvents, lithium salts, LiNO3, and TTFEB are pre-mixed and injected into the initial battery cell, this approach leads to competitive reactions among the functional components in the same chemical environment. LiNO3 and TTFEB decompose simultaneously on the surface of the negative electrode current collector, resulting in a disordered chemical composition, non-uniform structure, and difficulty in fully utilizing the functions of each component in the formed SEI film. This application proposes a multi-stage synergistic strategy for high-voltage lithium metal batteries: "prioritized interface construction + localized high-concentration host construction." Based on a deep understanding of the SEI film formation mechanism, it identifies differences in the optimal reaction conditions for different film-forming components: LiNO3 requires a low-viscosity ether environment and non-competitive conditions for sufficient reaction, while TTFEB requires controlled decomposition rates to form a dense LiF layer.

[0110] The integration of chemical deposition and electrochemical activation in the first stage transforms the originally loose LiNO3 reduction products into a structurally stable inner SEI base with good ion conductivity. The low-rate charge-discharge during the first formation process promotes the optimization of Li3N crystallization and Li... x NO y The structural rearrangement resulted in a denser and more uniform inner layer structure. Based on a deep understanding of the SEI formation mechanism, a fundamental improvement in the quality of the inner SEI film was achieved through the synergistic effect of chemistry and electrochemistry.

[0111] In conventional technologies, although LiNO3 is widely used as an additive for lithium metal anodes, it is usually used in combination with other components, and its reduction product is Li3N / Li x NO y Often dispersed within the SEI film, it is difficult to form a continuous and stable protective layer. The embodiments of this application, through a dual-functional design in the first stage, provide sufficient electrolyte wetting and ensure preferential reaction of LiNO3 during the pre-formation process through the relative enrichment of LiNO3. More importantly, it integrates the pre-formation process to "activate" and "solidify" the chemically deposited LiNO3 derivatives through electrochemical means.

[0112] Conventional SEI membrane modification strategies often aim to form a protective layer with a single property, such as a pure LiF layer or a pure polymer layer, which struggles to simultaneously meet multiple requirements such as mechanical strength, ion conduction, chemical stability, and volume adaptability. This application proposes a functionally graded SEI membrane design concept of "flexible inside, rigid outside," which systematically constructs a bilayer structure with clearly defined functional divisions through a multi-stage process: an inner layer of Li3N / Li... x NO y It provides mechanical flexibility and ion conduction channels, enabling it to adapt to volume changes during lithium metal charging and discharging; the outer LiF-rich layer provides extremely high chemical stability and electronic insulation, effectively blocking electrolyte decomposition and electron tunneling.

[0113] This gradient structure is not a simple physical superposition, but a chemical construction achieved through precise timing control and interface engineering. Strong chemical bonding and structural transitions exist between the inner and outer layers, ensuring the overall structural stability of the SEI. More importantly, this design concept resolves the inherent contradictions of a single SEI film: rigid layers are prone to breakage, and flexible layers lack sufficient strength. The functionally gradient design achieves complementary and synergistic performance enhancement.

[0114] The lithium metal battery manufacturing method provided in this application can also combine pulsed electrolyte injection with programmed cooling. During the second electrolyte injection stage, the initial high temperature reduces the viscosity of LHCE to promote rapid penetration, while subsequent cooling provides suitable kinetic conditions for the controlled decomposition of TTFEB and the ordered crystallization of LiF. This "thin-layer growth" mode promotes the uniform and dense deposition of LiF, significantly improving the protective effect of the outer SEI film. This synergistic process design represents a shift in technological concept from "passive acceptance" to "active regulation."

[0115] In summary, the embodiments of this application achieve precise control of the lithium metal anode interface through multi-dimensional innovations, including a multi-stage synergistic injection strategy, pulsed injection process, temperature gradient control, pressure-assisted permeation, and step-by-step formation. These innovations are not only reflected in the design of specific process parameters, but more importantly, they establish a novel interface engineering paradigm: achieving the orderly construction of complex interfaces through time-series control and multi-dimensional collaboration. This technical approach opens up new avenues for the practical application of high-voltage lithium metal batteries and provides valuable insights for other electrochemical systems requiring precise interface control.

[0116] Accordingly, another embodiment of this application also provides a lithium metal battery, which is prepared using the lithium metal battery manufacturing method described in the above embodiments. For parts that are the same as or corresponding to the previous embodiment, please refer to the corresponding descriptions in the foregoing embodiments; detailed descriptions will not be repeated below.

[0117] Lithium metal batteries can be classified into cylindrical batteries, prismatic batteries, and pouch batteries according to their battery type.

[0118] According to some embodiments of this application, another aspect of this application also provides an energy storage system, including a lithium metal battery as described in the above embodiments.

[0119] The energy storage system includes a battery pack, an energy management system (EMS), a battery management system (BMS), and an energy storage converter (PCS), wherein the battery pack includes multiple lithium metal batteries as described in the above embodiments.

[0120] According to some embodiments of this application, in another aspect of this application, an electrical device is provided, the electrical device including a load and the lithium metal battery in the above embodiments; or, the electrical device including a load and the energy storage system in the above embodiments.

[0121] Electrical equipment includes vehicles, household appliances, electric motors, medical equipment, scientific research instruments, and power grids.

[0122] The following are specific embodiments of this application. In all the following embodiments, a pouch cell battery is used as the unified testing platform, and the capacity of the lithium metal battery is 3Ah~5Ah.

[0123] The batteries of the examples and comparative examples were prepared in the following manner.

[0124] (1) Provide positive electrode, negative current collector and separator.

[0125] The cathode material will use NCM811 (LiNi) 0.8 Co 0.1 Mn 0.1 O2) was used as the active material. The positive electrode was prepared by mixing NCM811, conductive agent Super P, carbon nanotubes and binder PVDF in N-methylpyrrolidone in a mass ratio of 94:2.5:0.5:3 to form a slurry, which was then coated onto an aluminum foil current collector with a thickness of 12 μm. The coating surface density was controlled at 20 ± 0.5 mg / cm³. 2 The compacted density is 3.3 g / cm³. 3 .

[0126] The negative electrode current collector uses a high-purity lithium metal foil with a thickness of 50μm (purity ≥99.9%).

[0127] The diaphragm is a PP / PE / PP three-layer composite diaphragm with a thickness of 20μm.

[0128] (2) Initial cell assembly was carried out in a dry chamber with a dew point below -45°C, and the ambient humidity was strictly controlled to prevent lithium metal oxidation. The positive electrode, separator, and lithium metal negative electrode were stacked and wound into a core, and then sealed with an aluminum-plastic film. The assembled initial cell was vacuum dried at 80°C for 24 hours to ensure that the residual moisture inside the initial cell was less than 20 ppm, creating favorable conditions for the subsequent electrolyte injection process. All electrolyte preparations were completed in a high-purity argon glove box (O2 < 1 ppm, H2O < 1 ppm), and strict atmosphere control ensured the purity and stability of the electrolyte.

[0129] (3) Inject the first electrolyte into the initial cell. The formula of the first electrolyte is shown in Table 1. The amount of the first electrolyte injected accounts for 70% to 85% of the total amount of electrolyte injected. After the electrolyte injection is completed, the initial cell is placed in a constant temperature environment of 30°C for 4 hours to allow the electrolyte to fully penetrate into the microporous structure of the electrode.

[0130] (4) Charge the initial cell to 3.0V with a constant current of 0.02C and let it stand for 10 minutes to stabilize the voltage; then charge it to 3.8V with a constant current of 0.05C and then discharge it to 2.5V at the same rate. Repeat this charging and discharging process twice. The temperature of the first formation process is controlled at 30±2℃. The initial cell is aged at 35℃ for 12 hours.

[0131] (5) A second electrolyte is injected into the initial cell using a pulse injection method. The formulation of the second electrolyte is shown in Table 1, and the injection volume of the second electrolyte accounts for 20% to 30% of the total injection volume. The mass of each pulse injection accounts for 20% to 33% of the total mass of the second electrolyte, and the pulse interval is 15 min to 30 min. The pulse injection process is accompanied by temperature gradient control. The initial temperature is set at 45℃ to reduce the viscosity of the high-concentration electrolyte, and then gradually reduced to 30℃ at a rate of about 0.5℃ / min. After the injection is completed, a pressure of 0.2 MPa is applied and maintained for 10 min to further promote the uniform distribution of the electrolyte deep in the electrode.

[0132] (6) The initial cell undergoes a second formation process, which consists of three steps: the first step involves two charge-discharge cycles at a low current of 0.05C (voltage range 2.5V~4.2V) to gently activate the interface system; the second step increases the charge-discharge cycle to 0.2C (2.0V~4.4V) three times to stabilize the basic structure of the SEI; the third step further increases the charge-discharge cycle to 0.5C (1.5V~4.6V) five times to complete the final formation of the SEI. The temperature of the entire formation process is controlled at 30℃~35℃ to ensure the stability and controllability of the interface reaction.

[0133] In Table 1, all formulations are calculated using the internal addition method, where the actual solvent mass equals 100 minus the mass percentage of lithium salt and additives, multiplied by the percentage of each solvent in the total solvent. The values ​​for DME, DOL, G3, and SL in the table represent the mass percentage of each solvent in the total solvent, and the sum of these four values ​​always equals 100%. LiFSI is expressed as molar concentration (mol / L), and LiNO3 and TTFEB are expressed as mass percentage (wt%). The content of these additives is calculated based on the total mass of the electrolyte at each stage. The electrolyte injection ratio indicates the percentage of electrolyte in each stage relative to the total injected electrolyte volume. Comparative Example 1 in Table 1 uses a conventional injection method, injecting the electrolyte into the initial cell in one step.

[0134] Table 1

[0135] The examples and comparative examples underwent initial coulombic efficiency testing, 25°C cycling performance testing, 45°C cycling performance testing, 60°C high-temperature storage testing, and electrochemical impedance spectroscopy testing.

[0136] Initial Coulombic Efficiency Test: At 25℃, the film is charged at a constant current rate of 0.5C to the upper limit voltage of 4.5V, then charged at a constant voltage until the current drops to 0.05C, and finally discharged at a constant current rate of 0.5C to the lower limit voltage of 2.8V. The initial coulombic efficiency (ICE) is calculated using the following formula: ICE = (initial discharge capacity / initial charge capacity) × 100%. This indicator directly reflects the degree of irreversible loss of active lithium during SEI film formation. A high-quality SEI film should have a high initial coulombic efficiency.

[0137] The 25°C cycling performance test includes three rate conditions: (1) 0.5C rate test: 0.5C constant current charging to 4.5V, constant voltage charging to 0.05C cutoff, and then 0.5C constant current discharging to 2.8V; (2) 2C rate test: 2C constant current charging to 4.5V, constant voltage charging to 0.05C cutoff, and then 2C constant current discharge to 2.8V; (3) 5C rate test: 5C constant current charging to 4.5V, constant voltage charging to 0.05C cutoff, and then 5C constant current discharge to 2.8V.

[0138] The discharge capacity was recorded for the 1st, 100th, 200th, and 500th cycles under each rate condition. Capacity retention was calculated using the following formula: Capacity retention (%) = (Nth discharge capacity / 1st discharge capacity) × 100%. This test aims to evaluate the long-term stability of the SEI film and the cyclic reversibility of the lithium metal anode under different rate stresses.

[0139] The 45°C cycling performance test was conducted using the same three-rate conditions as the 25°C cycling performance test, and the capacity retention rate was recorded at the 100th, 200th, and 500th cycles. By comparing the performance differences at room temperature and high temperature, the protective effect of the gradient SEI structure constructed in this application embodiment under extreme conditions can be evaluated.

[0140] 60°C High-Temperature Storage Test: The battery was charged and discharged once at 25°C at a 1C rate, and the discharge capacity was recorded as the initial capacity C1. The battery was then charged to 100% SOC (4.5V constant voltage charging to 0.05C cutoff) and stored in a 60°C constant temperature chamber for 30 days. After storage, the battery was left to stand at room temperature for 2 hours, and then a complete charge-discharge cycle was performed, recording the recovered capacity C2. The capacity recovery rate was calculated using the following formula: Capacity recovery rate (%) = (C2 / C1) × 100%. This indicator reflects the chemical stability of the SEI film at high temperatures and its ability to inhibit electrolyte decomposition.

[0141] Electrochemical impedance spectroscopy (EIS) testing was conducted at 50% SOC of the battery, with a frequency range of 100 kHz to 0.01 Hz, an AC amplitude of 10 mV, and a test temperature of 25 °C. Test time points included: after formation (initial state), 100 cycles, 200 cycles, and 500 cycles under 0.5C conditions during the 25 °C cycle performance test. Electrochemical impedance spectroscopy is an important method for characterizing interfacial properties and can quantitatively evaluate the ion transport characteristics and stability of the SEI film.

[0142] The test results are shown in Tables 2 to 8.

[0143] Table 2

[0144] Table 3

[0145] Table 4

[0146] Table 5

[0147] Table 6

[0148] Table 7

[0149] Table 8

[0150] According to the initial coulombic efficiency in Table 2, the initial coulombic efficiencies of Examples 1 to 6 all exceed 95%, with Example 3 reaching the highest value of 96.5%. In contrast, the initial coulombic efficiencies of the comparative examples are all below 94%, especially Comparative Example 5, which is only 89.5%. This significant difference directly reflects the fundamental difference in the initial SEI film formation process. The multi-stage synergistic liquid injection process used in Example 1 creates a non-competitive reaction environment for LiNO3 in the first stage, allowing it to preferentially form a uniform and dense Li3N / Li3 on the lithium anode surface. x NO y In the inner layer, this process consumes relatively little active lithium and the resulting product exhibits good ion conductivity. Subsequently, in the second stage, the decomposition rate of TTFEB is precisely controlled through pulsed injection, uniformly depositing a LiF-rich outer layer on the existing substrate, avoiding excessive lithium consumption caused by rapid, disordered decomposition. In contrast, the single-stage mixed injection in Comparative Example 1 caused LiNO3 and TTFEB to react competitively simultaneously, resulting in a disordered chemical composition and uneven thickness of the formed SEI film, leading to greater irreversible lithium loss. Comparative Example 5, due to the use of a high-viscosity sulfone solvent in the first stage, severely affected electrolyte wetting and initial film quality, thus exhibiting the lowest initial coulombic efficiency.

[0151] Tables 2 to 4 reveal deeper differences in interface stability based on room temperature cycling performance data. At 25°C and a 0.5C rate, Example 1 retains 89.3% of its capacity after 500 cycles, while Comparative Example 1 retains only 78.2%, showing a significant difference in decay rate. This difference is even more pronounced at higher rates; after 500 cycles at a 5C rate, Example 1 retains 78.5% of its capacity, while Comparative Example 1 drops to 60.2%. Combined with EIS data analysis, the fundamental difference in interface evolution can be clearly seen: the total interface resistance of Example 1 slowly increases from an initial 45Ω to 95Ω after 500 cycles, an increase of only 111%; while that of Comparative Example 1 increases sharply from an initial 82Ω to 245Ω, an increase of 199%. This difference in impedance evolution stems from the fundamental difference in the SEI film structure. The gradient functional SEI constructed in Example 1 has the characteristics of "flexible inside and rigid outside," with the inner layer Li3N / Li... x NO y The SEI can adapt to volume changes in lithium metal without breaking, and the dense outer LiF layer provides a stable chemical barrier. The synergistic effect of these two elements allows the SEI to maintain its structural integrity during long-term cycling. In contrast, the disordered SEI in Comparative Example 1 continuously breaks and reconstructs under cyclic stress, leading to a continuous increase in interfacial impedance and a continuous loss of active lithium.

[0152] The difference between Comparative Example 2 and Example 1 specifically verifies the importance of pulsed injection. Although the electrolyte composition and injection ratio were exactly the same in both examples, Comparative Example 2, which used a continuous injection method, had a significantly lower capacity retention rate (83.0%) after 500 cycles than Example 1 (89.3%), and its interfacial impedance increased more rapidly (185Ω vs 95Ω). This demonstrates that pulsed injection, through a "thin-layer growth" mode, can indeed form a denser and more uniform LiF outer layer, while continuous rapid injection leads to excessively high local concentrations of TTFEB, resulting in a loose and porous LiF layer formed by rapid decomposition, and a significant decrease in protective effect.

[0153] Comparative Examples 3 and 4 verified the indispensability of LiNO3 and TTFEB, respectively. The lack of LiNO3 in Comparative Example 3 resulted in the ineffective formation of the inner SEI layer, with a capacity retention of only 72.5% after 500 cycles and an interfacial impedance as high as 285 Ω, representing the most severe deterioration among all samples. This fully demonstrates the crucial role of the LiNO3-derived inner layer in providing mechanical support and ion transport channels. While Comparative Example 4 showed acceptable initial performance due to the lack of TTFEB, the absence of a dense LiF outer layer led to continuous electrolyte decomposition at high voltages, resulting in rapid performance degradation, particularly at 5C high-rate conditions where only 64.0% of the capacity was retained after 500 cycles.

[0154] The high-temperature cycling data in Tables 5 to 7 further validate the superiority of the gradient SEI. Increased temperature accelerates electrolyte decomposition and interfacial side reactions, posing a more severe challenge to the stability of the SEI film. Example 1 maintained 83.5% capacity after 500 cycles at 0.5C at 45°C, a decrease of only 5.8 percentage points compared to room temperature, demonstrating excellent temperature adaptability. In contrast, Comparative Example 1, under the same conditions, showed a capacity retention rate of 68.0%, a decrease of 10.2 percentage points compared to room temperature, indicating significantly higher temperature sensitivity. This difference stems from the chemical stability of the LiF-rich outer layer. LiF possesses extremely high thermodynamic stability and a wide electrochemical window, effectively blocking the intensified electrolyte decomposition reaction at high temperatures. Storage tests at 60°C further confirmed this, with the capacity recovery rates of the examples generally exceeding 88%, with Example 2 reaching as high as 93.2%, while the comparative examples were all below 86%, especially Comparative Example 5 at only 75.0%. This indicates that the gradient SEI film constructed in this application maintains good chemical stability even under extreme high-temperature static conditions, effectively suppressing self-discharge and interfacial corrosion.

[0155] Data from Examples 2 through 6 validated the optimization potential and robustness of the process parameters. Example 2, by increasing the LiNO3 concentration to 5 wt%, achieved the lowest initial interfacial impedance (42 Ω) and the best high-temperature storage performance (93.2%), indicating that moderately increasing LiNO3 helps strengthen the inner SEI layer. Example 3, by increasing TTFEB to 60 wt%, achieved the highest initial coulombic efficiency (96.5%), but with a slight increase in interfacial impedance, indicating the existence of an optimal concentration range. Examples 4 and 5 validated the process window for the injection ratio; although the performance decreased slightly with ratios of 70:30 and 85:15, they were still significantly better than the comparative example, demonstrating the process's tolerance. Example 6, by reducing the number of pulses from 5 to 3, showed limited performance degradation, indicating the potential for process simplification and optimization.

[0156] Based on the above test data, this application successfully achieved precise control of the interface of high-voltage lithium metal batteries through a multi-stage synergistic liquid injection process. Compared with the traditional single-stage liquid injection process, cycle life is improved by more than 40%, high-temperature stability by more than 30%, and interface impedance is reduced by 45%. These performance improvements are not achieved through expensive new materials, but rather through ingenious process design that fully leverages the potential of existing materials. It is particularly noteworthy that this process can be implemented on existing production lines through equipment modification, without requiring investment in entirely new production facilities. The tolerance of process parameters (liquid injection ratio 70%~85%, pulse count 3~5 times) provides ample operational window for industrial implementation. With the rapid growth in demand for high-energy-density batteries in the electric vehicle and energy storage markets, the lithium metal battery manufacturing method provided in this application provides a feasible technical path to achieve high-energy-density lithium metal batteries with a specific energy of over 500Wh / kg, and has significant industrial application value.

[0157] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.

Claims

1. A method for manufacturing a lithium metal battery, characterized in that, include: We provide positive electrode plates, negative electrode current collectors, and separators; The positive electrode, the negative current collector, and the separator are wound or stacked and then placed into a housing to form an initial battery cell. The separator is located between the positive electrode and the negative current collector. A first electrolyte is injected into the initial battery cell. The first electrolyte includes lithium salt, lithium nitrate and solvent, and the solvent contains at least 70 wt% of short-chain ether solvent, wherein the short-chain ether solvent has less than or equal to 6 carbon atoms. The initial battery cell undergoes a first formation process; A second electrolyte is injected into the initial cell using a pulse injection method. The second electrolyte includes lithium salt, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and a solvent. The molar concentration of lithium salt in the second electrolyte is greater than that in the first electrolyte. The initial cell is subjected to a second formation process to form the lithium metal battery.

2. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, In the first electrolyte, the concentration of lithium salt is 0.3 mol / L to 2.5 mol / L; in the second electrolyte, the concentration of lithium salt is greater than 2.5 mol / L and less than or equal to 6.0 mol / L.

3. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, In the second electrolyte, the mass percentage of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is 35wt% to 70wt%.

4. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, The second formation process includes: The initial battery cell is subjected to a first charge-discharge cycle using a first rate, and the voltage range is a first voltage range. The initial battery cell is subjected to a second charge-discharge cycle using a second rate, with the voltage range being the second voltage range; The initial battery cell is subjected to a third charge-discharge cycle using a third rate, within the third voltage range. Wherein, the third multiplier > the second multiplier > the first multiplier; the first voltage range is within the second voltage range, and the second voltage range is within the third voltage range.

5. The method for manufacturing a lithium metal battery according to claim 4, characterized in that, The first multiplier is 0.01C~0.15C, the second multiplier is 0.1C~0.5C, and the third multiplier is 0.2C~1.0C; the first voltage range is 2.0V~4.5V, the second voltage range is 1.5V~4.6V, and the third voltage range is 1.0V~4.8V.

6. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, After performing the first formation process on the initial battery cell, before injecting the second electrolyte into the initial battery cell, the process further includes: a static aging treatment, which includes at least one aging cycle in which the initial battery cell is heated from a first temperature to a second temperature and then cooled back to the first temperature within a preset time.

7. The method for manufacturing a lithium metal battery according to claim 6, characterized in that, The preset time is 0.5h to 48h, the first temperature is 25℃ to 30℃, and the second temperature is 45℃ to 50℃.

8. The method for manufacturing a lithium metal battery according to claim 6 or 7, characterized in that, After the static aging treatment and before injecting the second electrolyte into the initial cell, the following steps are performed: testing the interface impedance of the initial cell; if the interface impedance of the initial cell is in the range of 20Ω to 100Ω, then injecting the second electrolyte into the initial cell; if the interface impedance of the initial cell is greater than 100Ω, then performing the static aging treatment again; if the interface impedance of the initial cell is less than 20Ω, then performing charge-discharge cycles at a current of 0.02C once to twice.

9. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, During the process of injecting the second electrolyte into the initial cell, the mass of electrolyte injected in each pulse is 5% to 50% of the mass of the second electrolyte, the pulse interval is 2 min to 60 min, and the number of pulses is 2 to 20.

10. The method for manufacturing a lithium metal battery according to claim 9, characterized in that, Before injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is raised to a first preset temperature; During the process of injecting the second electrolyte into the initial battery cell, the temperature of the initial battery cell is reduced from the first preset temperature to the second preset temperature.

11. The method for manufacturing a lithium metal battery according to claim 1, characterized in that, In the second electrolyte, the solvent includes ether solvents and sulfone solvents, wherein the mass ratio of the sulfone solvent to the ether solvent is 20:80 to 80:

20.

12. The method for manufacturing a lithium metal battery according to claim 11, characterized in that, In the first electrolyte, the solvent also includes sulfone solvents; in the mixed system of the first electrolyte and the second electrolyte, the mass ratio of the sulfone solvent to the ether solvent is 20:80 to 50:

50.

13. A lithium metal battery, characterized in that, It is prepared by the manufacturing method of lithium metal battery as described in any one of claims 1 to 12.

14. An energy storage system, characterized in that, Including the lithium metal battery as described in claim 13.

15. An electrical appliance, characterized in that, The electrical device includes a load and a lithium metal battery as described in claim 13; or, the electrical device includes a load and an energy storage system as described in claim 14.

Citation Information

Patent Citations

  • Charging-discharging type electrolyte injection process of lithium ion battery

    CN108417770A

  • Multi-tab lithium ion battery and preparation method thereof

    CN114300751A

  • Lithium metal battery, manufacturing method thereof and electric equipment

    CN120357049A

  • Lithium metal battery, manufacturing method thereof and electric equipment

    CN120767433A

  • Lithium metal battery, manufacturing method thereof and electric equipment

    CN120767434A